Inflammatory Neuropathy Cause and Treatment (INCAT) Scale for the assessment of disability level in patients with chronic inflammatory demyelinating polyneuropathy: linguocultural ratification in Russia - А. S. Arestova; Е. А. Melnik; A. B. Zaytsev; A. A. Zimin; А. Yakubu; E. S. Sherbakova; D. G. Yusupova; D. A. Grishina; N. A. Suponeva; M. A. Piradov (Нервно-мышечные болезни)
Background. Chronic inflammatory demyelinating polyneuropathy (CIDP) is a treatable dysimmune polyneuropathy. An objective response for pathogenic therapy is essential in diagnosis and management of CIDP. For proper assessment of patient’s complaints and evaluation of disease progression, it is recommended to use validated scales and questionnaires. The paper presents the results of the first step of Inflammatory Neuropathy Cause and Treatment (INCAT) validation in patients with CIDP.Objective: the development of the Russian version of the INCAT scale and its linguocultural ratification.Materials and methods. 15 patients with definite CIDP (according to EFNS/PNS criteria) were enrolled. Linguocultural ratification was conducted according to the standard protocol.Results. The Russian version of the INCAT scale was developed.Conclusion. We conducted the first stage of INCAT scale validation in patients with CIDP.